Exploring the Effectiveness of STEAM-Based Courses on Junior High School Students’ Scientific Creativity - Tran, Ngoc-Huy; Huang, Chin-Fei; Hung, Jeng-Fung (Frontiers in Education, 2021)
The purpose of this study is exploring the effectiveness of STEAM (Science, Technology, Engineering, Arts, Mathematics)-based curriculum on junior high school students’ scientific creativity. The main topic of STEAM-based curriculum in this study is about ancient mechanical clock which was designed and produced by authors’ team. Further, the main concept of ancient mechanical clock is about gear wheel. Hence, this study designed two stages of courses which were gear wheel science courses (two weeks) and STEAM-based courses (two weeks). Sixty-two junior high school students from two different courses participated in this study and were divided into control group and experimental group. This study adopted counterbalance designed. The control group joined gear wheel science courses first and joined STEAM-based courses then. Adversely, the experimental group joined STEAM-based courses first. Both groups were asked to complete a pre-test, interim-test and post-test by completing the “Scientific Creativity Test (Cronbach’s α .87)”. The results from paired t-test analysis show that control group students did not perform significant differences of scientific creativity between joining gear wheel science courses before and after, but they got significant higher scores after joining STEAM-based courses than before. On the other hand, the experimental group students got higher scores of scientific creativities after joining STEAM-based courses than before and persisted in getting higher scores after joining gear wheel courses than before. Furthermore, the results implied that the STEAM-based course might can help students maintain or continue their scientific creativity ability. Further discussion is provided.